Comparison of In Situ and Ex Situ Equilibrium Passive Sampling for Measuring Freely Dissolved Concentrations of Parent and Alkylated Polycyclic Aromatic Hydrocarbons in Sediments. (22nd September 2020) - Reininghaus, Mathias; Parkerton, Thomas F.; Witt, Gesine
Abstract: Equilibrium passive sampling methods (EPSMs) allow quantification of freely dissolved contaminant concentrations ( C free ) in sediment porewater. Polydimethylsiloxane (PDMS) is a convenient sampling polymer that can be equilibrated in field (in situ) or laboratory (ex situ) sediments to determine C free, providing reliable compound‐specific PDMS–water partition coefficients ( K PDMS‐water ) are available. Polycyclic aromatic hydrocarbons (PAHs) are an important class of sediment contaminants comprised of parent and alkylated homologs. However, application of EPSM to alkylated PAHs is challenged by lack of K PDMS‐water measurements. Our first objective was to obtain K PDMS‐water for 9 alkylated PAHs and biphenyls using 3 different PDMS‐coated fibers. Quantitative relationships were then established to define K PDMS‐water for 18 parent and 16 alkyl PAHs included in the US Environmental Protection Agency's sediment quality benchmark method for benthic life protection based on additive toxic units. The second objective was to compare C free in porewater obtained using both in situ and ex situ EPSMs at 6 Baltic Sea locations. The results indicated that in situ and ex situ C free for alkyl PAHs generally agreed within a factor of 3. Further, all sites exhibited additive toxic units <1, indicating that PAHs pose a low risk to benthos. The results extend practical application of EPSMs for improved risk assessment and derivation of porewater‐based remediation goals for PAH‐contaminated sediments. Environ Toxicol Chem 2020;39:2169–2179. © 2020 SETAC